Management of children with congenital nephrotic syndrome: challenging treatment paradigms - ALPAY, HARİKA (OXFORD UNIV PRESS, 2019)
Background. Management of children with congenital nephrotic syndrome (CNS) is challenging. Bilateral nephrectomies followed by dialysis and transplantation are practiced in most centres, but conservative treatment may also be effective. Methods. We conducted a 6-year review across members of the European Society for Paediatric Nephrology Dialysis Working Group to compare management strategies and their outcomes in children with CNS. Results. Eighty children (50% male) across 17 tertiary nephrology units in Europe were included (mutations in NPHS1, n = 55; NPHS2, n = 1; WT1, n = 9; others, n = 15). Excluding patients with mutations in WT1, antiproteinuric treatment was given in 42 (59%) with an increase in S-albumin in 70% by median 6 (interquartile range: 3-8) g/L (P< 0.001). Following unilateral nephrectomy, S-albumin increased by 4 (1-8) g/L (P = 0.03) with a reduction in albumin infusion dose by 5 (2-9) g/kg/week (P = 0.02). Median age at bilateral nephrectomies (n = 29) was 9 (7-16) months. Outcomes were compared between two groups of NPHS1 patients: those who underwent bilateral nephrectomies (n = 25) versus those on conservative management (n = 17). The number of septic or thrombotic episodes and growth were comparable between the groups. The response to antiproteinuric treatment, as well as renal and patient survival, was independent of NPHS1 mutation type. At final follow-up (median age 34months) 20 (80%) children in the nephrectomy group were transplanted and 1 died. In the conservative group, 9 (53%) remained without dialysis, 4 (24%; P< 0.001) were transplanted and 2 died. Conclusion. An individualized, stepwise approach with prolonged conservative management may be a reasonable alternative to early bilateral nephrectomies and dialysis in children with CNS and NPHS1 mutations. Further prospective studies are needed to define indications for unilateral nephrectomy.
Keywords: bilateral nephrectomies; congenital nephrotic syndrome; genotype-phenotype correlation; management approach; NPHS1; DIFFUSE MESANGIAL SCLEROSIS; STEROID-RESISTANT; GENOTYPE/PHENOTYPE CORRELATIONS; GLOMERULAR PROTEIN; 1ST YEAR; MUTATIONS; NPHS1; NEPHRIN; SURVIVAL; LIFE